Comparison of physiological and post-endovascular aneurysm repair infrarenal blood flow. Issue 3 (17th February 2017) - Raptis, Anastasios; Xenos, Michalis; Georgakarakos, Efstratios; Kouvelos, George; Giannoukas, Athanasios; Labropoulos, Nicos; Matsagkas, Miltiadis
Abstract: Endovascular aneurysm repair (EVAR) of abdominal aortic aneurysms results in redirection of blood through the deployed endograft (EG). Even though EVAR is clinically effective, the absolute flow restoration is not warranted. Our purpose was to compare the physiological with the post-EVAR infrarenal flow conditions. We developed patient-specific models based on computed tomography data of five healthy volunteers and ten patients treated with the Endurant ® stent-graft system. Wall shear stress (WSS), helicity, pressure and velocity fields were calculated using computational fluid dynamics. The results showed a decrease of peak WSS on the part of the EG that resides in the iliac arteries, compared to the physiological value ( p  = 0.01). At the abdominal part, the average helicity seems to increase after EVAR, while at the iliac arteries part, the intensity of helical flow seems physiological. Pressure drop and peak velocity in the iliac arteries part are lower than the physiological values ( p  = 0.04). The comparison revealed that most hemodynamic properties converge to normal levels at the abdominal part whereas statistically significant variations were observed in the iliac arteries part. The delineation of the differences between physiological and postoperative flow data could pave the way for the improvement of EG designs.